Perancangan Prototipe Digitalisasi Pengelolaan Asrama Berbasis Web terhadap Optimalisasi Peminjaman Fasilitas - Permatasari, Ayrin Lucyani; Gunardi, Felicia; Acarya, I Wayan Maha; Wijaya, Matthew; Geraldo, Ryo Kenzie; Ningsih, Rahmi Yulia; Pratiwi, Chairani Putri (Journal of Informatics, Electrical and Electronics Engineering, 2025)
A dorm is more than simply a place for students to live, it's also a place for them to socialize and develop their personalities, which has a big impact on both academic and non-academic aspects. In order to guarantee the residents' comfort, managing the needs of the dorm is essential. Errors in data recording, a lack of transparency in borrowing data, and ineffective coordination and communication are issues that frequently occur in the manual process of borrowing facilities. This study proposes an innovative approach for digitalizing dormitory facilities management, bringing all resident demands together on a single centralized platform. This prototype helps by eliminating the need for direct contact, which is frequently less efficient, and offering capabilities that save all data in a single database. The goal of this project is to create a web-based prototype that meets the requirements of dorm occupants and aids in resolving problems and difficulties that arise. Design thinking (empathize, define, ideate, prototype, test) was the methodology employed in this study. It began with direct observation to identify difficulties, followed by the creation of a prototype and a questionnaire for measuring user satisfaction. According to the results of the questionnaire, 88.79% of users expressed satisfaction with the system, particularly with regard to its usability, navigability, and attractive interface. With this system, the efficacy and simplicity of managing dormitory demands and facilities has improved.